The Pattern of Sexual Interest of Female-to-Male Transsexual Persons With Gender Identity Disorder Does Not Resemble That of Biological Men: An Eye-Tracking Study - Akira Tsujimura; Hiroshi Kiuchi; Tetsuji Soda; Kentaro Takezawa; Shinichiro Fukuhara; Tetsuya Takao; Yuki Sekiguchi; Atsushi Iwasa; Norio Nonomura; Yasushi Miyagawa (Sexual Medicine, 2017)
Introduction: Very little has been elucidated about sexual interest in female-to-male (FtM) transsexual persons. Aims: To investigate the sexual interest of FtM transsexual persons vs that of men using an eye-tracking system. Methods: The study included 15 men and 13 FtM transsexual subjects who viewed three sexual videos (clip 1: sexy clothed young woman kissing the region of the male genitals covered by underwear; clip 2: naked actor and actress kissing and touching each other; and clip 3: heterosexual intercourse between a naked actor and actress) in which several regions were designated for eye-gaze analysis in each frame. The designation of each region was not visible to the participants. Main Outcome Measures: Visual attention was measured across each designated region according to gaze duration. Results: For clip 1, there was a statistically significant sex difference in the viewing pattern between men and FtM transsexual subjects. Longest gaze time was for the eyes of the actress in men, whereas it was for non-human regions in FtM transsexual subjects. For clip 2, there also was a statistically significant sex difference. Longest gaze time was for the face of the actress in men, whereas it was for non-human regions in FtM transsexual subjects, and there was a significant difference between regions with longest gaze time. The most apparent difference was in the gaze time for the body of the actor: the percentage of time spent gazing at the body of the actor was 8.35% in FtM transsexual subjects, whereas it was only 0.03% in men. For clip 3, there were no statistically significant differences in viewing patterns between men and FtM transsexual subjects, although longest gaze time was for the face of the actress in men, whereas it was for non-human regions in FtM transsexual subjects. Conclusion: We suggest that the characteristics of sexual interest of FtM transsexual persons are not the same as those of biological men. Tsujimura A, Kiuchi H, Soda T, et al. The Pattern of Sexual Interest of Female-to-Male Transsexual Persons With Gender Identity Disorder Does Not Resemble That of Biological Men: An Eye-Tracking Study. Sex Med 2017;5:e169–e174.